Altered microbial resource limitation regulates soil organic carbon sequestration based on ecoenzyme stoichiometry under long‐term tillage systems. (4th August 2022) - Song, Xiaojun; Li, Jingyu; Liu, Xiaotong; Liang, Guopeng; Li, Shengping; Zhang, Mengni; Zheng, Fengjun; Wang, Bisheng; Wu, Xueping; Wu, Huijun
Abstract: Soil microbial metabolism is critically important for regulating soil carbon (C) sequestration. However, how soil organic C (SOC) stock responds to the changes in microbial resource limitation and microbial C use efficiency (CUE) under long‐term tillage system remains uncertain. Soil samples were randomly collected from a long‐term (19 years) tillage experiment growing winter wheat with three treatments [i.e., moldboard‐plough without straw retention (MPN), no‐tillage with straw retention (NTS), and subsoiling with straw retention (SSS)] and an adjacent natural grassland (GRL) in 2018. We analyzed microbial resource limitation and CUE based on ecoenzyme stoichiometry. Results revealed that the reduction of soil bulk density and total dissolved nitrogen (N) resulted in an increased vector angle. Higher total dissolved N and lower vector length jointly led to higher CUE under long‐term conservation tillage practices (i.e., NTS and SSS). Notably, the higher CUE and soil available phosphorus as well as the lower N limitation both directly contributed explaining the increase in SOC stock under conservation tillage practices. Overall, long‐term conservation tillage practices could alleviate microbial resource limitation by enhancing available nutrients to promote SOC sequestration. Our study provides new knowledge to enhance the understanding of SOC stock regulated by microbial resource limitations and microbial C use efficiency.